A Comparison of Online Games and Pictures Instruction in the Context of EFL to Enhance Students’ Vocabulary Achievement - Wenas, Beauty Gatari Cathleen; Tobing, Caroline V. Katemba (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2016)
The purpose of this study is to find the enhancement of students’ vocabulary achievement using Online Games and Pictures Instruction. This study used quantitative research method and comparative design. This study was designed to seek the answer to the following question: Is there any significant difference on the students’ vocabulary enhancement between those who are taught using Online Games and Pictures Instruction? In order to answer that question, there were two classes in grade eight of SMP Perguruan Advent XV Ciracas, Jakarta Timur. They were divided into two groups, grade 8-a was Pictures Instruction group and grade 8-b was Online Games group. The vocabulary test (pre-test) was given at the first meeting. After 16 hours of treatment, the post-test was administered to both groups to see the significant of both methods. The data was analyzed using SPSS 17. The normalized gain of the students who are taught using Online Games 0.2802. It can be concluded that the gain level of Online Games is low. While the normilezed gain of the students who are taught using Pictures Instruction is 0.4631. It can be concluded that the gain level of it can be concluded that the gain level of Picture Instruction is average. The obtained result through the normalized gain indicated there was a significant difference between the group which was taught through Online Games and Pictures Instruction. Based on the result of the data the null hypothesis was rejected and some recommendations are given at the end. Key Word: vocabulary, teaching, Online Games, Picture Instruction